Learning and instruction in the digital age: Introduction - Ifenthaler, Dirk (2010)
The modern digital age is characterized by powerful information and communication technologies that can have a significant impact on learning. The 2008 CELDA (Cognition and Exploratory Learning in the Digital Age) conference in Freiburg featured a number of papers that addressed the intersecting areas of knowledge, pedagogy, and technology. Individualized and independent learning has been made possible by the Internet and Web 2.0 technologies. However, the advances reported in this volume and presented at CELDA are likely to be hardly more than a footnote in the history of educational technology if advances continue at such a hectic pace. In the not-so-distant future, we might see the genuine meaning of constructivism emerge as learners become active constructors of their own learning environments, setting individual goals and creating content structures for the knowledge and content they intend to master. © 2010 Springer-Verlag US.